DESCRIPTION OF KNOWLEDGE WOMEN PREGNANT ON FIRST TRIMESTER ABOUT HYPEREMESIS GRAVIDARUM IN REGIONAL HEALTH CENTER TIRON MULTIPLICATION DISTRICT OF KEDIRI - Luqmanasari, Endah (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2018)
Hyperemesis Gravidarum is excessive nausea and vomiting, causing disruption of daily activities and even to endanger the lives of pregnant women. Besides, also with hyperemesis gravidarum is severe nausea and vomiting that can lead to daily work was interrupted, and the general state of the mother to be bad. The purpose of this study is to describe the first trimester pregnant mother knowledge about hyperemesis gravidarum in Regional Health Center Tiron multiplication District of Kediri. Design The design of this study descriptive research with cross sectional approach, This study was conducted on 1-10 August 2017. All pregnant women in the first trimester Tiron Regional Health Center Kediri District of multiplication with a population of 35 respondents, with accidental sampling technique obtained a sample of 30 respondents. The variable in this study is an independent variable (Single) ie Iu Overview first trimester pregnant knowledge about hyperemesis gravidarum. The research instrument used a questionnaire that was tested for validity and reliability. Data processing includes editing, coding, Scoring, Tabulating. Percentage receipts and data analysis. The results showed 30 respondents ie the first trimester pregnant women with hyperemesis gravidarum mostly knowledgeable enough that a number of 17 respondents (56.6%), Good 3 respondents (10%) and less 10 respondents (33%). Then for the first trimester pregnant women who have knowledge about the understanding of hyperemesis gravidarum Good number of 13 respondents (43.3%), insufficient knowledge about the causes of hyperemesis gravidarum number of 16 respondents (53.3%). Enough knowledge about the diagnosis hyperemesis gravidarum number of 17 respondents (56.6%). Lack of knowledge about prevention hyperemesis gravidarum number of 16 respondents (53.3%). Based on the results of these studies concluded that the knowledge of the first trimester pregnant women in Region Health Center Tiron multiplication District of Kediri have sufficient knowledge of 17 respondents (56.6%). Advised on health personnel to augment the knowledge counseling to pregnant women, especially for the first trimester have extensive knowledge about hyperemesis gravidarum.